The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/jsfa.10863
|View full text |Cite
|
Sign up to set email alerts
|

Monoglyceride oleogels as fat replacers in filling creams for sandwich cookies

Abstract: BACKGROUND Many food products need to be reformulated to reduce the intake of saturated and trans fats which are considered unhealthy. In particular, the reformulation of filling creams (FCs) is challenging as these fats cannot be directly replaced with liquid oil without affecting the final product properties. This research studied the formulation and characterization of FCs for sandwich cookies using monoglyceride oleogel as fat material. RESULTS FC formulated with 260 g kg−1 oleogel showed viscoelastic modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…Initially, the oil loss was 4.1 ± 0.4% for the RP sample (T0), and significantly similar for R4SB (6.25 ± 0.4%), R5SB (4.93 ± 0.4%), R6SB (4.86 ± 0.4%), R5SF (4.9 ± 0.4%) and R6SF (4.53 ± 0.4%). A similar result was found for HPMC and MC oleogel‐filling in canola oil after 24 h of analysis (Tanti et al, 2016) and in MG‐oleogels in cream fillings with lower lipid content (≥26%) (Palla et al, 2020).…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…Initially, the oil loss was 4.1 ± 0.4% for the RP sample (T0), and significantly similar for R4SB (6.25 ± 0.4%), R5SB (4.93 ± 0.4%), R6SB (4.86 ± 0.4%), R5SF (4.9 ± 0.4%) and R6SF (4.53 ± 0.4%). A similar result was found for HPMC and MC oleogel‐filling in canola oil after 24 h of analysis (Tanti et al, 2016) and in MG‐oleogels in cream fillings with lower lipid content (≥26%) (Palla et al, 2020).…”
Section: Resultssupporting
confidence: 76%
“…The highest exudation observed in our samples was in agreement with the oily appearance observed in Figure 1 and can be attributed to the presence of oil bubbles as observed in Figures 2 and 3 for this sample, which confirms that this sample in both oils was not very well structured. This difference between oleogel and shortening fillings was noticed after 4 days for cream filling (Palla et al, 2020) or 10 days for praline fillings (Si et al, 2016). Palla et al (2020) also found that the oil loss was directly related to the amount of lipid in the filling, since the sample with the highest lipid (oleogel) content (40%) showed the highest oil loss (around 30% after 21 days).…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations